Pentingnya Strategi Pemasaran bagi Pelaku UMKM di Wilayah Kabupaten Bantul Provinsi DIY - Widyastuti, Niken; Dwiyanto, Bambang Sugeng; Nuralam; Jemadi; Sabardini, Sri Ekanti (Cattleya Darmaya Fortuna, 2025)
The purpose of this community service is to provide an understanding of the importance of marketing strategies both offline (conventional) and online. Partners in this community service are MSME actors in Bantul Regency, DIY Province. MSMEs have become a crucial business and have contributed greatly to creating jobs, proven to be able to absorb labor. Therefore, MSME actors need an understanding, insight and marketing strategy skills for the progress of MSMEs. So that later MSME actors in Bantul Regency will be able to improve their ability to determine marketing strategies or add skills to determine marketing strategy steps optimally in the future. The current community service method has been implemented in two ways, namely lecture and training methods. The results of this community service activity can improve the abilities or skills of MSME actors in Bantul Regency. It is hoped that after the community service activity, MSME actors in Bantul Regency will be able to increase sales or increase profits because they have realized the importance of marketing strategies, and can also utilize marketing strategies optimally. The results of the activity stated that the participants were very enthusiastic and paid attention to all series of events, both during the material training and practice.